Prognosis and immune landscape of bladder cancer can be predicted using a novel miRNA signature associated with cuproptosis - Zhilei Zhang; Fang Liu; Yongbo Yu; Fei Xie; Tao Zhu (PeerJ)
Background Bladder cancer is characterized by a high recurrence rate and mortality, posing a significant challenge to clinical management. Recently, cuproptosis, a novel form of regulated cell death, has been identified as a potential target for therapeutic intervention in various diseases. The contribution of cuproptosis-related microRNAs (miRNAs) in bladder cancer pathogenesis, however, remains largely unexplored. Therefore, the current study aims to construct a miRNA signature related to cuproptosis for predicting the prognosis and facilitating personalized therapeutic strategies in bladder cancer patients. Methods In this study, we retrieved transcriptomic data and clinical information pertaining to bladder cancer from publicly available databases, including the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). We identified a set of 19 cuproptosis-related genes through a comprehensive review of relevant literature. Using multivariate Cox regression and LASSO analysis, we constructed a cuproptosis-related miRNA prognostic signature. The Kaplan-Meier (K-M) and receiver operating characteristic (ROC) curves were used to validate the accuracy of prediction. Additionally, we developed a nomogram incorporating clinical characteristics and the miRNA signature to further assess its prognostic value. We evaluated the tumor microenvironment (TME) of every patient using immune ESTIMATE, CIBERSORT, and ssGSEA algorithms. We also investigated the differences in tumor mutation burden (TMB) and drug sensitivity between two groups. Finally, we validated the prognostic value of this miRNA signature using the OncomiR dataset. Results We developed a panel of eight cuproptosis-associated miRNAs to serve as a prognostic signature. The predictive validity of this signature was determined using Kaplan-Meier and ROC curves, and was found to be acceptable in both the TCGA training, test and total dataset. The prognostic value of this signature was confirmed by univariate and multivariate Cox regression analysis, indicating its applicability as a prognostic factor. The immune cell infiltration was significantly associated with an immunosuppressive phenotype of TME in the high-risk group of patients; meanwhile, patients in the high-risk group had a lower TMB resulted in shorter survival. Notably, higher estimate scores and IC50 value for chemotherapy drugs were observed in the high-risk group, indicating poor response to immune therapy and chemotherapy.